2015
DOI: 10.1056/nejmoa1507854
|View full text |Cite
|
Sign up to set email alerts
|

Bivalirudin or Unfractionated Heparin in Acute Coronary Syndromes

Abstract: BACKGROUNDConflicting evidence exists on the efficacy and safety of bivalirudin administered as part of percutaneous coronary intervention (PCI) in patients with an acute coronary syndrome. METHODSWe randomly assigned 7213 patients with an acute coronary syndrome for whom PCI was anticipated to receive either bivalirudin or unfractionated heparin. Patients in the bivalirudin group were subsequently randomly assigned to receive or not to receive a post-PCI bivalirudin infusion. Primary outcomes for the comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
328
8
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 348 publications
(353 citation statements)
references
References 26 publications
9
328
8
8
Order By: Relevance
“…level (5). A number of clinical trials (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) have led to fast and great advancements in the development of effective anticoagulant and antiplatelet drugs (23). ▶ Figure 2 highlights a selection of important large-scale trials that studied antiplatelet and/or anticoagulant treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…level (5). A number of clinical trials (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) have led to fast and great advancements in the development of effective anticoagulant and antiplatelet drugs (23). ▶ Figure 2 highlights a selection of important large-scale trials that studied antiplatelet and/or anticoagulant treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a novel pharmacomechanical strategy based on the use of transradial access site and bivalirudin infusion has been proposed at the time of PCI for ACS patients in the MATRIX trial [68]. The MATRIX trial showed that radial as compared with femoral access reduced net adverse clinical events, through a reduction in major bleeding and all-cause mortality [69], while no significant differences were observed with bivalirudin as compared with unfractionated heparin [70].…”
Section: Antiplatelet Therapy Optimization: From Inflammation To Acutmentioning
confidence: 99%
“…Second, the more frequent use of a radial access for PCI, which is associated with lower bleeding risk as compared with femoral access (16). Randomized trials conducted in this era of potent P2Y 12 antagonists with a more prevalent use of radial access have shown no difference in the risk of composite ischemic events, albeit that the risk of stent thrombosis (particularly acute stent thrombosis) was consistently higher with bivalirudin, but these trials have yielded inconsistent results as regards to the bleeding benefit which was previously noted with bivalirudin (17)(18)(19)(20). In a meta-analysis of randomized trials comparing both agents for patients undergoing PCI via radial access, bivalirudin was not associated with a lower risk of bleeding compared with unfractionated heparin (21).…”
mentioning
confidence: 99%